Representasi Tokoh Oda Nobunaga dalam Game Samurai Warriors 4 - Pandu Satria Mandala Putra; Taqdir Taqdir; Fithyani Anwar; Nursidah Nursidah (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2026)
This study analyzes the representation of Oda Nobunaga in the video game Samurai Warriors 4 using Ferdinand de Saussure’s semiotic approach. The research aims to identify how visual elements, dialogues, and narrative structures construct the image of Nobunaga within the game. This study employed a descriptive qualitative method with data collected through gameplay observation, screenshot documentation, and dialogue transcription from the story mode of the game. The analysis focused on eight selected scenes that prominently featured Oda Nobunaga and contained significant visual and verbal elements related to character design, leadership interactions, and military strategy. The analysis focused on the relationship between signifier and signified in visual and verbal representations of the character. The findings reveal that Oda Nobunaga is represented as a powerful, charismatic, strategic, and dominant military leader. Visual signs such as golden armor, red cloak, facial expressions, and battle gestures symbolize authority, ambition, and military dominance. Verbal signs through dialogues further reinforce Nobunaga’s image as an authoritarian and strategic leader. In addition, battle scenes and campaign narratives reconstruct Nobunaga as a central figure in the unification of Japan during the Sengoku period. The study also shows that historical figures in video games undergo dramatization and symbolic reconstruction to fit contemporary narrative and entertainment purposes. Therefore, Samurai Warriors 4 functions not only as entertainment media but also as a cultural representation that shapes players’ perceptions of historical figures in popular culture.